Academic performance and use of psychoactive drugs among healthcare students at a university in southern Brazil: cross-sectional study - Boclin, Karine de Lima Sírio; Cecílio, Fernanda Fabian Callejon; Faé, Gabriela; Fanti, Gabriela; Centenaro, Guilherme; Pellizzari, Thoany; Gaviolli, Emanuela; Mario, Débora Nunes; Rigo, Lilian (São Paulo Medical Journal, 2020)
BACKGROUND: People have been using psychoactive substances for a long time. Over the last few years, this practice has spread among university students, who use these substances to improve their academic performance, relieve stress and increase concentration and memory. OBJECTIVES: To estimate the use of psychoactive drugs among healthcare students at a higher education institution in the city of Passo Fundo (RS), Brazil, and to ascertain the associated demographic and lifestyle factors. DESIGN AND SETTING: Cross-sectional study in a higher education institution. METHODS: We included 287 undergraduate medicine and dentistry students in this study. They answered a self-administered questionnaire regarding sociodemographic, lifestyle and health variables. The statistical analysis used univariate and bivariate analyses with Pearson’s chi-square test (P-value < 0.05). Multivariate analyses were used to estimate odds ratios (OR) and their respective 95% confidence intervals. The SPSS software, version 20.0, was used. RESULTS: The prevalence of use of psychoactive substances among the students was 24.7%. Among these students, high frequencies of psychoactive drugs had been prescribed by physicians (95.8%) and for the purpose of relaxation or stress relief (73.2%). Women, medical students (compared with dental students) and participants with lower academic performance were more likely to use psychoactive drugs. After the multivariate adjustment, the “course” and “academic performance” remained associated with use of psychoactive drugs. CONCLUSION: There was high prevalence of psychoactive drug use among the students at the higher education institution investigated. Some variables (female sex, medical students and low academic performance) were associated with the outcome.